Tantalum versus titanium acetabular component in single-stage hip revision for periprosthetic joint infection: a comparative analysis of implant survivorship - Zhaoxi Xue; Wentao Guo; Wenbo Mu; Boyong Xu; Li Cao (Journal of Orthopaedics and Traumatology)
Abstract Background The impact of tantalum (Ta) versus titanium (Ti) acetabular components on reinfection risk in periprosthetic joint infection (PJI) remains controversial. While prior studies have focused on two-stage revisions, this is the first comparative analysis of Ta versus Ti in single-stage revisions. This study aimed to compare all-cause rerevision and infection recurrence rates between Ta and Ti acetabular components in single-stage revision for chronic PJI. Materials and methods In this study, all patients underwent single-stage revision combined with intra-articular (IA) antibiotic infusion, with 56 receiving Ta acetabular components and 79 receiving Ti components. Both the Ta and Ti groups utilized acetabular reconstruction methods (including cups with and without augments) and cementless prostheses for all femoral components. We compared implant survivorship between the two groups, using implant survivorship free from reinfection and all-cause revision as the endpoints. Multivariate logistic regression (MVLR) was used to determine the independent predictive factors for septic failure. Results The implant survivorship free from reinfection of the Ta group (92.9%; 95% confidence interval (CI) 85.7~98.2%) was comparable to that of the Ti group (88.6%; 95% CI 81.0~94.9%; P = 0.391; log-rank test). The implant survivorship free from all-cause rerevision of the Ta group (91.1%; 95% CI 84.1~100%) was comparable to that of the Ti group (87.3%; 95% CI 78.9~94.4%; P = 0.323; log-rank test). MVLR did not identify the Ta acetabular component (P = 0.414) as a protective factor against septic failure in acetabular reconstruction. However, previous revision (P = 0.048) was identified as a risk factor. Conclusions Ta acetabular components exhibited a risk of all-cause rerevision comparable to Ti components in single-stage revision, with no significant protective effect against reinfection. These findings suggest that the notion of Ta components preventing infections should be viewed with caution.